2010
DOI: 10.3354/meps08820
|View full text |Cite
|
Sign up to set email alerts
|

Density- and trait-mediated effects of fish predators on amphipod grazers: potential indirect benefits for the giant kelp Macrocystis pyrifera

Abstract: Indirect effects of predators on primary producers may arise when predators suppress herbivore abundance and/or alter the behaviour patterns of herbivores in ways that reduce grazing pressure. Most studies highlight the role of predators in reducing herbivore abundance (i.e. densitymediated interactions), while behavioural effects (i.e. trait-mediated interactions) induced by predators are less commonly considered and are often assumed to be of secondary importance. We used a mesocosm experiment to evaluate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 58 publications
1
6
0
Order By: Relevance
“…Previous research has indicated that fishes eat kelp mesograzers and may control their abundance (Davenport & Anderson 2007, Pérez-Matus & Shima 2010. Our results ex pand on this to show that kelp forest fishes, particularly higher trophic level fishes, depend on kelp mesograzers, and thus on kelp itself, for a significant portion of their dietary carbon.…”
Section: Discussionsupporting
confidence: 76%
“…Previous research has indicated that fishes eat kelp mesograzers and may control their abundance (Davenport & Anderson 2007, Pérez-Matus & Shima 2010. Our results ex pand on this to show that kelp forest fishes, particularly higher trophic level fishes, depend on kelp mesograzers, and thus on kelp itself, for a significant portion of their dietary carbon.…”
Section: Discussionsupporting
confidence: 76%
“…It is most likely explained by the structurally complex granite stone habitat that provided shelter from fish predation, but at the same time appears to have reduced the grazing pressure of gammarids on algae growing on the top part of the stones. Such cascading predator effects on primary producers mediated by changes in herbivore behavior are well known to cause strong trophic cascades in various ecosystems (Werner and Peacor , Peckarsky et al , Pérez‐Matus and Shima , Carr and Boyer ). Consequently, we propose that in situ warming, by increasing predation pressure on, and predation risk for, gammarid herbivores, strengthened a trophic cascade that benefitted the filamentous algae.…”
Section: Discussionmentioning
confidence: 99%
“…ͳͳ Epifaunal abundance can be affected by fish predation and, by regulating the presence of mesograzers, invertivore fishes may even play a role in macroalgae performance (Moksnes et al, 2008;Pérez-Matus and Shima, 2010;Reynolds and Sotka, 2011). Dictyota is known as a chemically-defended seaweed against fishes (Hay, Duffy et al, 1987;, which turns it into a good choice of habitat for mesograzers (Christie et al, 2003(Christie et al, , 2009Duffy and Hay, 1991;Hay, 1997).…”
Section: Algae Biomass Fluctuationmentioning
confidence: 99%